Equity Risk Incentives and Corporate Tax Aggressiveness - REGO, SONJA OLHOFT; WILSON, RYAN (Journal of Accounting Research, 2012)
ABSTRACT This study examines equity risk incentives as one determinant of corporate tax aggressiveness. Prior research finds that equity risk incentives motivate managers to make risky investment and financing decisions, since risky activities increase stock return volatility and the value of stock option portfolios. Aggressive tax strategies involve significant uncertainty and can impose costs on both firms and managers. As a result, managers must be incentivized to engage in risky tax avoidance that is expected to generate net benefits for the firm and its shareholders. We predict that equity risk incentives motivate managers to undertake risky tax strategies. Consistent with this prediction, we find that larger equity risk incentives are associated with greater tax risk and the magnitude of this effect is economically significant. Our results are robust across four measures of tax risk, but do not vary across several proxies for strength of corporate governance. We conclude that equity risk incentives are a significant determinant of corporate tax aggressiveness.